Characteristics of Coconut Coir Composite Acoustic with Epoxy Matrix - Lia Solikhatul Amalia; Andi Fadllan; Abdul Wahib (Journal of Natural Sciences and Mathematics Research, 2015)
The aim of this research is to measure the absorption coefficient of composite material synthesized from coconut fiber as filler and epoxy matrix and to discover the alternative interval of sound reducer material from natural resources, i.e (coconut fiber : fine fiber, rough fiber and crude fiber). After pressing, the sample was then cutted and examined using Bruel and Kjaer characterization. From the characterization process, the absorption coefficient of composite with filler of fine, rough and crude coconut fiber is calculated and found to be 0.997, 0.97 and 0.96, respectively. © 2015 JNSMR UIN Walisongo. All rights reserved.